2009
DOI: 10.1097/mej.0b013e32832d048b
|View full text |Cite
|
Sign up to set email alerts
|

First aid and basic life support training for first year medical students

Abstract: We developed 24 and 12-h programs for first aid and basic life support (FA-BLS) training for first-year medical students and evaluated the opinions of both the trainers and trainees on the effectiveness of the programs. The trainees were the first-year students of academic years 2000-2001 (316 students) and 2001-2002 (366 students). The evaluations of the participants were collected from short questionnaires created specifically for the study. For the 24-h training program, most of the students stated that FA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
2
5
0
1
Order By: Relevance
“…[2] Another advantage of training students in first aid would be that they can be successful peer first aid trainers for others as opined by 97.7% medical students in Altintaş et al . study[15] and also reported in a Turkish study. [16] These measures will ensure that an increased number of first aid trainers are available at a time of any calamity faced by the people.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…[2] Another advantage of training students in first aid would be that they can be successful peer first aid trainers for others as opined by 97.7% medical students in Altintaş et al . study[15] and also reported in a Turkish study. [16] These measures will ensure that an increased number of first aid trainers are available at a time of any calamity faced by the people.…”
Section: Discussionsupporting
confidence: 69%
“…[915] Students in a New Zealand study for example felt that the simulations were a reasonable measure of their abilities and 91% felt that such simulations should be included in their end-of-year assessment. As current medical undergraduate training does not ensure new graduates can intervene effectively in an emergency, these simulation based workshops should be incorporated into the undergraduate curriculum both for education and assessment of competence in emergency management.…”
Section: Discussionmentioning
confidence: 99%
“…ECHR work experience, together with previous healthcare-related education, were both associated with higher training amount and student confidence in own expertise in the included procedures as well, and both were independently important when effects of the concurrent factors were adjusted for. These results were in line with reports from other studies,8 19–22 although some have found no such relationship 12…”
Section: Discussionsupporting
confidence: 93%
“…17,18 Desde seu ingresso na faculdade, logo nos primeiros meses, os estudantes já são cobrados pela sociedade e por eles mesmos a agirem como médicos, esperando que tenham as mesmas habilidades de um profissional. 19,20 Por isso, defendemos que o treinamento para o atendimento à PCR faça parte do currículo do curso de medicina, 12 onde o SBV seria ensinado logo no primeiro ano e o SVA mais no final do curso quando o estudante já possui uma carga maior de conhecimento, habilidades e logo estará trabalhando na assistência a pessoas. Entendemos que os cursos do American Heart Association (AHA) -por exemplo, o Basic Life Support (BLS) e o Heart Saver -e da Sociedade Brasileira de Cardiologia (Treinamento de Emergências Cardiovasculares Básico -TECA B) atendem as necessidades do treinamento para profissionais da saúde já formados ou para uma população leiga.…”
Section: Introductionunclassified